Olografia e sistemi di comunicazione avanzati per i sotterranei del Castello di Otranto - Fernando Cesaria (mediaGEO soc. coop., 2017)
The latest frontiers of holography and the use of beacon communication systems provide new models of exploitation and enjoyment of cultural heritage goods. The application of these technologies at the Castle of Otranto (Lecce) enhance the tourists' experience, giving life to the underground and immersing the visitor in the Middle Age. Holographic installations connected to advanced control systems create a point of contact between the tourist and the people who have written the history of the Castle. In order to transform the traditional guided-tour to an interactive and experiential guided tour, the system also provides two apps accessible from mobile devices: an audio guide dedicated to foreign tourists and an application dedicated to the tourist guide for controlling the holographic installations and for monitoring visitors.